Could vitamin D concentration be a marker of a long hospital stay in older adults patients? - Nowak, Justyna; Jabczyk, Marzena; Jagielski, Paweł; Hudzik, Bartosz; Brukało, Katarzyna; Borszcz, Jakub; Zubelewicz-Szkodzińska, Barbara (Frontiers in Nutrition, 2023)
Background and aims. Vitamin D plays pleiotropic role in human body. Some studies have suggested that hypovitaminosis D may serve as a marker of comorbidity severity and length of hospital stay. Hospitalized elderly patients with a higher comorbidity burden tend to have lower vitamin D status, which negatively impacts the length of their hospital stay. Vitamin D deficiency has been identified as a significant risk factor for a prolonged hospital stay. The study aims to investigate the link between vitamin D status and prolonged hospital stays, focusing on geriatric patients, as well as to assess the variation in hospitalization duration among geriatric patients with differing vitamin D statuses.Methods. The studied sample was conducted of 422 patients admitted to the geriatric department aged over 60 years. Blood samples were collected in the morning on the day of admission. Patients was divided into two group (deficiency group and named suboptimal group) according to the diagnostic threshold defining serum 25(OH)D concentration approved for Central Europe. Patients were divided into two groups based on hospitalization duration: the first, "shorter hospitalization," included stays up to 11 days, while the second, "longer hospitalization," encompassed stays of 12 days and above.Results. The study involved 242 Caucasian patients, primarily women (172 women, 70 men).Patients with vitamin D deficiency had extended hospital stays compared to those with vitamin D levels below 49.